Utilization of biomass ash generated from combined heat and power generation system as a multi-nutrient source for crops - Tirthankar Mohanty; Subhaprada Dash; Priyabrata Pattanaik; Hara Prasada Tripathy; J.M.L. Gulati; Dilip Kumar Mishra; William Holderbaum (International Journal of Thermofluids)
The present study on the development of a protocol to obtain plant nutrients from biomass ash was carried out in the Faculty of Agricultural Sciences and Institute of Technical Education and Research, Siksha ‘O’ Anusandhan, Deemed to be University, Bhubaneswar, Odisha, India, as part of the laboratory study. The study addresses the dual challenges of managing biomass from agricultural waste, fertility towards its use as plant health tonic vis-a-vis crop nutritional needs in an eco-friendly manner and also utilizing the heat evolved during the combined heat and power (CHP) generation system can also be utilized to produce bio-energy. Biomass ash, a valuable by-product of CHP systems, contains essential nutrients that can be repurposed to improve crop nutrition and soil health. The current gap lies in the need for systematic methods to convert this ash into compelling multi-nutrient compositions for agricultural use by developing a standardized process. The protocol includes the collection of crop residues like rice, maize and groundnut from the homogenous fields of respective crops at harvest as part of the initial study. The crop residue was mixed separately in a proper manner to obtain a consolidated composite sample for each crop. These samples were sun-dried for 72 h to remove the excess moisture as part of partial drying and then burned in earthen pots in open condition to obtain ash sample and collected separately for each crop. From the stock sample, 8 g of ash sample was grounded to obtain fine ash powder by using a mortar and pestle for 60 min. A uniform ash mixture comprising of rice, maize and groundnut was obtained through repeated steps by mixing 2 g of the grounded ash taken from 8 g stock of each crop and mixed layer-wise. This crop residue mixture was then subjected to calcination at different temperature ranging from 450 °C with an incremental increase of 100 °C up to 750 °C for 4 h using a muffle furnace and a crop residue based mixture was obtained having a multi-nutrient composition. The study revealed that the mixture of the three crop residues in 1:1:1 ratio produced more number of nutrients in noticeable concentration at calcination temperature of 550 °C. The study further provides a scope to integrate this protocol towards obtaining a nutrient mixture from biomass ash generated from a combined heat and power generation system as an alternative to landfill use. Thus, by integrating this method into modern agricultural production systems, it is possible to obtain plant health tonic and reducing landfill waste and methane emissions from decomposing organic matter and enhance soil health and agricultural productivity sustainably. This research highlights the potential of leveraging biomass ash generated from biomass combined heat and power (CHP) generation systems in an eco-friendly manner for sustainable farming systems, including self-power generation for agriculture mills.